2020
DOI: 10.1038/s41598-019-57166-4
|View full text |Cite
|
Sign up to set email alerts
|

The fatigue-induced alteration in postural control is larger in hypobaric than in normobaric hypoxia

Abstract: www.nature.com/scientificreports www.nature.com/scientificreports/ cardio-ventilatory responses. For all three conditions, HR increase and was significantly higher at POST compare to PRE without interaction between the conditions HH, NH and NN (Table 2). Inversely for SpO 2 no time effect was found, but a significant difference (lower values) for HH vs. NN (p < 0.001) and NH vs. NN (p < 0.001) were observed at PRE and POST. BF in HH was significantly higher to NH and NN (p < 0.001) only at PRE. Scientific Repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…In this study, normobaric hypoxia detrimentally affected the balance (~7%), when subjects were exposed to a simulated altitude of ~3,800 m. This is in line with previous studies that have demonstrated elements of impaired balance, such as postural stability (Cymerman et al, 2001 ; Degache et al, 2020 ) and body sway (Nordahl et al, 1998 ; Wagner et al, 2011 ) in simulated altitude (2,400 m to 5,500 m) vs. normoxia, with exposure durations of a few minutes to 24 h in non-athletic populations. However, this study corroborates and extends these findings by revealing detrimental effects of HYP on balance even in highly trained basketball players who engage in activities demanding high levels of balance.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In this study, normobaric hypoxia detrimentally affected the balance (~7%), when subjects were exposed to a simulated altitude of ~3,800 m. This is in line with previous studies that have demonstrated elements of impaired balance, such as postural stability (Cymerman et al, 2001 ; Degache et al, 2020 ) and body sway (Nordahl et al, 1998 ; Wagner et al, 2011 ) in simulated altitude (2,400 m to 5,500 m) vs. normoxia, with exposure durations of a few minutes to 24 h in non-athletic populations. However, this study corroborates and extends these findings by revealing detrimental effects of HYP on balance even in highly trained basketball players who engage in activities demanding high levels of balance.…”
Section: Discussionsupporting
confidence: 91%
“…As a result, reduced activation of the muscles encompassing the joints (e.g., the ankles and knees) may inherently prevent unwanted and uncontrollable joint oscillations when performing the SLBT (Keller et al, 2012 ). Additionally, considering that vision is one of the first senses to be affected by acute hypoxia (Nordahl et al, 1998 ; Degache et al, 2020 ) and that the SLBT was performed with open eyes, the elite group may have been able to compensate for reduced vision capacity through greater contributions from vestibular and proprioceptive sensory information (Paillard et al, 2002 , 2011 ; Pojskic et al, 2020 ). In brief, it is well-documented that the role of the visual system on balance performance decreases with higher playing level in athletes (Paillard and Noé, 2006 ; Paillard et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations